Leadership of Vocational High School Principals in Developing Teaching Factories and Students’ Entrepreneurial Mindsets and Their Impact on the Quality of Vocational School Graduates: A Systematic Literature Review - Handepi, Nogi; Gangga, Almes; Maiharni , Yetti; Giatman, M.; Sukardi, Sukardi (The Future of Education Journal, 2026)
Background: Vocational High Schools (SMK) face the challenge of high Open Unemployment Rate (TPT) of 11.13% in 2021, indicating a gap between graduate competencies and industrial needs. Principal leadership with entrepreneurial competence is key in developing Teaching Factory (TEFA) and cultivating students' entrepreneurial spirit. Objective: To analyze the role of SMK principal leadership in developing Teaching Factory, strategies for fostering students' entrepreneurial spirit, supporting and inhibiting factors, and its impact on graduate quality based on a systematic literature study. Methods: Literature review analyzing 28 research articles (2014-2024) from SINTA accredited journals, academic databases, and policy documents. Analysis method: thematic analysis with stages of familiarization, coding, theme search, review, theme definition, and report writing. Results: (1) SMK principal leadership with strong entrepreneurial competence creates innovative learning, builds conducive work culture, and develops DUDI partnerships through three pillars: innovation, work culture, and sustainable partnerships; (2) Strategies for fostering entrepreneurial spirit include curriculum integration, extracurricular programs, real business practices, and habituation of entrepreneurial culture; (3) Supporting factors include principal commitment, teacher competence, infrastructure, DUDI partnerships, policy support, and student motivation; inhibiting factors include limited HR/facilities, limited capital, unsustainable partnerships, and work culture misalignment; (4) Positive impact on graduate quality includes improved technical/non-technical competence, entrepreneurial spirit formation, industry absorption rate, and entrepreneurial capability, with percentage of entrepreneurial graduates still below target (< 50% within 12 months). Conclusion: Transformational SMK principal leadership with entrepreneurial competence is a determining factor in Teaching Factory implementation and students' entrepreneurial spirit development. However, systemic obstacles such as infrastructure limitations, teacher competence, DUDI partnership sustainability, and absence of holistic policy require strengthening systemic support from government, education offices, and all vocational education stakeholders.